Billy Graham and the rise of the Republican South - Miller, Steven P. (Steven Patrick), 1977- (Politics and culture in modern America., 2009)
Billy Graham and the Rise of the Republican South considers the critical role the famous evangelist played in creating the modern American South. Author Steven P. Miller treats Graham as a serious actor and a powerful transitional symbol--an evangelist, first and foremost, but also a profoundly political figure.